2016
DOI: 10.3390/ijms17101559
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characterization and in Vivo Antimycobacterial Studies of Panchovillin-Chitosan Nanocomposites

Abstract: Chitosan (CS, molecular weight 20.2 kDa, degree of deacylation (DD) 73.31%) was successfully obtained by deacetylation of chitin extracted from shrimp (Litopenaeus vannamei) shell wastes. The encapsulation of the bioactive natural product, panchovillin (PANV), isolated from Erythrina schliebenii, on a chitosan-tripolyphosphate (CS/TPP) nano-framework was achieved by ionotropic gelation. Characterization of pure CS, CS/TPP and PANV-CS/TPP nanocomposites was performed by FTIR, SEM and XRD. The molecular weight o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Furthermore D. melanogaster has been used as an infection model for M. abscessus and M. marinum , particularly to study the pathogenesis and metabolic consequences of mycobacterial infection [3841]. The larvae of G. mellonella have been widely used to study host-pathogen interactions for a range of microbes, including fungi, bacteria and viruses [1113,4245], but little has been reported using mycobacteria [35,4648], for which new in vivo infection models are greatly needed. Here we have demonstrated that this simple invertebrate model shows promise as a novel infection model for the M. tuberculosis complex.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore D. melanogaster has been used as an infection model for M. abscessus and M. marinum , particularly to study the pathogenesis and metabolic consequences of mycobacterial infection [3841]. The larvae of G. mellonella have been widely used to study host-pathogen interactions for a range of microbes, including fungi, bacteria and viruses [1113,4245], but little has been reported using mycobacteria [35,4648], for which new in vivo infection models are greatly needed. Here we have demonstrated that this simple invertebrate model shows promise as a novel infection model for the M. tuberculosis complex.…”
Section: Discussionmentioning
confidence: 99%
“…To understand the effect of a scaffold structure on the immobilized GOx, the chemical structures of [CS/TPP]­CC, [CS/Na]­CC, and [CS/TPP/Na]­CC before and after immobilizing GOx were analyzed by FTIR, as shown in Figure . For the electrodes before the immobilization of GOx, the broad peaks at 3432 cm –1 and the peaks at around 2900 cm –1 belong to the O–H bonds and C–H stretching of the CS, respectively. , In addition, the C–O–C asymmetric bond from 1061 to 1107 cm –1 and the CO double bond at 1643 cm –1 were also observed for the CS. For the electrodes after the immobilization of GOx, the FTIR peaks between 860 and 1100 cm –1 observed in GOx­[CS/TPP]­CC (blue line of Figure a), GOx­[CS/Na]­CC (orange line of Figure b), and GOx­[CS/TPP/Na]­CC (red line of Figure c) can be attributed to the phosphate buffer in the enzyme solution .…”
Section: Resultsmentioning
confidence: 93%
“…The GM larva has emerged as a simple and economical invertebrate model host to evaluate virulence of microbial pathogens and efficacy of antimicrobial compounds (Tsai, Loh, & Proft, 2016). Recent studies have validated the use of this model with mycobacteria and shown that larva lethality is species-dependent (Entwistle & Coote, 2018;Li et al, 2018;Meir, Grosfeld, & Barkan, 2018;Rwegasila, Mubofu, Nyandoro, Erasto, & Munissi, 2016).…”
Section: Disruption Of B11 Transcription Does Not Cause Attenuationmentioning
confidence: 99%